Integración, consistencia y transparencia de la experiencia Omnicanal del consumidor con relación a la intención de compra en tiendas departamentales en la categoría de prendas de vestir - Astete Meza, Arianne (2020)
Omnichannel retailers have received considerable attention from academics and professionals in recent years; however, its impacts on purchase intention and the results of the relationships between its variables are still unclear. Therefore, the objective of this study is to analyze the relationship of three components of the consumer's omnichannel shopping experience, such as integration, consistency and transparency, in respectant of purchase intention. The methodology of the study will be quantitative and the data will be collected through an online survey with 400 usable responses. The findings will indicate whether the components mentioned previously have a direct and significant impact on purchase intention. Finally, these findings will provide important scopes for theoretical discussions of future academics and research works.